Historical Patterns of Anthropogenic Impacts on Freshwaters in the Berlin-Brandenburg Region - Nützmann, Gunnar; Wolter, Christian; Venohr, Markus; Pusch, Martin (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
Since humans are preferentially settling in flood plains they often influence freshwater systems intensely. The first signs of anthropogenic impacts on surface waters in the Berlin-Brandenburg region are approximately 3000 years old. Considering the multiple and intense human uses of surface waters in this region, we analysed when, how and to which extent regional rivers and streams became impacted by dams, water mills and fish weirs resulting in changes in morphology, hydrology and ecological functioning. We hypothesise that the development and growth of cities in this region necessitated (1) efficient navigability of rivers linking them, (2) efficient use of hydropower resources for mills, and (3) significant pollution of surface waters especially with the beginning of industrial development. We analyse these hypotheses by means of three regional examples and delineate the effects of human uses on selected surface water bodies. Understanding the effects of these historic modifications of surface water supports the identification of options for a sustainable use of surface waters that are currently still subjected to multiple uses but face a significant decrease in discharge due to climate change.